2017
DOI: 10.4102/hsag.v22i0.1019
|View full text |Cite
|
Sign up to set email alerts
|

Strengths of families to limit relapse in mentally ill family members

Abstract: Background: Relapse prevention in mental health care is important. Utilising the strengths of families can be a valuable approach in relapse prevention. Studies on family strengths have been conducted but little has been done on the strengths of family members to help limit relapse in mental health care users. The purpose of this research was to explore and describe the strengths of family members in assisting mental health care users to limit relapses.Methods: A phenomenological design was followed. Purposive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Similarly, another study had reported that generally family members were supportive; they often expressed distress at having lost their sick relative, although he or she was just not the same person as before. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study had reported that generally family members were supportive; they often expressed distress at having lost their sick relative, although he or she was just not the same person as before. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Over recent decades, the responsibility of caregiving to people with severe mental illness has shifted from institutions to families, and family members are considered valuable resources for providing care and support to these patients (Tlhowe et al, 2017). Accordingly, some children and adolescents live with a mentally ill family member, participate in caregiving or even assume a primary caregiver role (Hinshaw, 2018).…”
Section: Introductionmentioning
confidence: 99%